Bibliometric study on the literature related to dental research and education published in Journal of Pakistan Medical Association - Adnan, Samira; Zafar, Kamil; Raza Khan, Farhan; Ullah, Rizwan (Journal of the Pakistan Medical Association, 2021)
Objective: To analyse characteristics of literature related to dental research and education published in a single medical journal. Method: The bibliometric study was conducted at the Sindh Institute of Oral Health Sciences, Jinnah Sindh Medical University from March till May 2020, and comprised electronic and hand search of scientific literature relevant to dentistry published in the Journal of Pakistan Medical Association from the first issue published in 1953 till March 2020. The selected articles were analysed for year of publication, field of study, type of article, institute and country of first author, number of authors and citation count. Keyword mapping was also carried out. Data was analysed using SPSS 19. Results: Of the 159 articles identified, 117(73.6%) were contributed from Pakistan. The most common specialties were oral and maxillofacial surgery and epidemiology with 20(12.6%) each, followed by operative dentistry and endodontics 19(11.9%). Majority of articles were Original / Research 87(54.7%). The highest number of articles were published in 2019 26(16.35%). The Aga Khan University, Karachi, contributed the most publications 30(18.9%), followed by Dow University of Health Sciences, Karachi, 11(6.9%). Majority of the articles were contributed by three authors 48(38.4%). The top cited article was found to have 113 citations, followed by 1(0.6%) each with 103 and 91 citations. Conclusions: The contribution of scientific papers related to dentistry and dental education in the Journal of Pakistan Medical Association was significant. With growth of dentistry as a discipline along with a parallel increase in the publication of dental research papers, Continuous...